High temperature CO2 sorption using Ca(OH)2 in pilot scale packed column - Preetham, Halugondanahalli Sadashivaiah; Madhu, Gattumane Motappa; Brijesh, Brijesh; Pai, K Vasantha Kumar (European Journal of Chemistry, 2016)
Carbon dioxide is the major content of greenhouse gases, which is released by many industries such as paper, cement and steel industries etc. Removal or separation of CO2 from the atmosphere is a challenging task for the researchers as it related to the human health and affects environment. Many methods and techniques have been tried for the removal of CO2, among them sorption method was found to be more simple and economical. Majority of research work related to CO2 sequestration was carried out using Thermo Gravimetric Analysis (TGA). In the present study an attempt was made to study high temperature CO2 sorption using self-fabricated packed bed column in pilot scale. In this work the absorption column was designed to utilize the flue gas temperature for effective sorption of carbon dioxide using Calcium hydroxide [Ca(OH)2] as a sorbent. The Ca(OH)2 was made into cylindrical extrudates. The gas mixture containing nitrogen and carbon dioxide was heated and subjected to CO2 sorption using Ca(OH)2. The sorption process for various temperatures was studied at a constant flow rate and fixed bed height. Concentration of CO2 was measured using a flue gas analyzer (NDIR sensors). The temperature was found to be major factor affecting sorption process. The optimum temperature was found to be 300 °C. Increase in the temperature above 300 °C, resulted in sintering and weight loss of the sorbent. The conversion of Ca(OH)2 to CaCO3 is confirmed by FT-IR, Scanning Electron Microscopy (SEM), Energy Dispersive X-Ray Analysis(EDAX) and XRD.